2018
DOI: 10.23996/fjhw.67815
|View full text |Cite
|
Sign up to set email alerts
|

Kanta-arkiston käyttökokemuksia työterveyshuollossa

Abstract: Sosiaali- ja terveysministeriön laatiman Sote-tieto hyötykäyttöön -strategian tarkoituksena on mahdollistaa, että terveydenhuollon ammattilaisella on käytössään ajantasainen potilastieto ja työtä tukevat tietojärjestelmät. Tietojen vaihto yli organisaatiorajojen toteutetaan valtakunnallisen Potilastiedon arkiston (Kanta-arkiston) avulla. Arkistoon on tallennettu tietoja lähes kaikista suomalaisista ja sen käyttö lisääntyy terveydenhuollon ammattilaisten keskuudessa koko ajan. Tutkimuksen tarkoituksena ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…1,[14][15][16][17][18]23,[25][26][27]30 Identified facilitators of use include perceived value of use 27 and usability (including user-friendliness, ease of use, and clarity). 11,14,16,28,31 Earlier studies have also identified factors that might hinder the use of (PA)EHRs. 5 For example, in the Netherlands, only 40% of the older users of a patient portal found it useful.…”
Section: Earlier Research On the Use Of Electronic Health Informationmentioning
confidence: 99%
“…1,[14][15][16][17][18]23,[25][26][27]30 Identified facilitators of use include perceived value of use 27 and usability (including user-friendliness, ease of use, and clarity). 11,14,16,28,31 Earlier studies have also identified factors that might hinder the use of (PA)EHRs. 5 For example, in the Netherlands, only 40% of the older users of a patient portal found it useful.…”
Section: Earlier Research On the Use Of Electronic Health Informationmentioning
confidence: 99%
“…Kauppinen et al, 2017), palvelujen käyttökokemuksia esimerkiksi työterveyshuollossa (esim. Nissinen et al, 2018) ja käyttökokemusten tiettyjä osa-alueita kuten turvallisuuteen liittyviä huolia (esim. Palojoki et al, 2016).…”
Section: Tuloksia Aikaisempi Tutkimus Keskittyy Vahvasti Käytettävyyteenunclassified
“…Previous studies have focused on perceptions of Kanta or other electronic health records (EHRs) among Finnish healthcare professionals (Nissinen, Soini, Leino, Hakulinen, & Saranto, 2018;Palojoki, Pajunen, Saranto, & Lehtonen, 2016) and pharmacists (Kauppinen, Ahonen, Mäntyselkä, & Timonen, 2017). In the autumn of 2015, a survey was conducted in 18 Finnish pharmacies on citizens' use of ePrescriptions and My Kanta (Lämsä, Timonen, Mäntyselkä, & Ahonen, 2017), but to the best of our knowledge, there are no earlier qualitative studies on how users, especially older adults, experience the My Kanta services.…”
mentioning
confidence: 99%